The Susceptibility of Malaysian Rice Brands To Sitophilus oryzae and The Potential Application of Zinc Oxide Nanoparticles For Control Purposes - Syanizam, Nurin Nazifa; Bakhori, Siti Khadijah Mohd; Hamzah, Siti Nasuha (Malaysian Applied Biology, 2024)
The rice weevil, Sitophilus oryzae, is an insect pest that can pose severe harm to stored grains. Rice weevils, both adults and larvae, cause significant economic losses because they can infest a wide range of plants and stored goods. Nanoparticle insecticides are created and studied to replace the overly-used synthetic chemical insecticides. The purpose of this study is to investigate the susceptibility of several commercialized rice brands towards S. oryzae infestation and to assess the toxicity of different types of zinc oxide (ZnO) against S. oryzae. The study involved twelve rice brands, and S. oryzae infestation rates were observed in the laboratory for 17 weeks. The infestation rates were obtained at the end of the observation period. To obtain the required dosages of 0.1, 0.2, 0.4, and 0.8% (w/w), four different concentrations of each type of ZnO nanoparticle that had undergone various reactivity modifications were mixed with rice for bioassays test. S. oryzae has been proven to be susceptible to almost all commercialized rice brands studied in this research. Based on the data, it can be concluded that the ZnO nanoparticle modified with gamma-ray is the most effective at controlling S. oryzae, as 100% mortality was seen after three days of treatment at concentrations between 0.4 to 0.08% (w/w). The slow emergence of pests in monitored rice brands is attributed to the protectants and their residue, which work by eradicating eggs and adults that have consumed the grain. Zinc oxide type 7A is the most toxic towards S. oryzae because of its exposure to gamma-ray which has the highest energy compared to neutron and beta rays. This results in the release of more active molecules to act on the pest.